PENGARUH STRUKTUR KEPEMILIKAN ASING DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI OLEH MYOPIC BEHAVIOUR - Melky Edward Buttang (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
This study aims to examine the effect of foreign ownership structure and audit quality on firm value that is tested directly or through myopic behavior. The sample used in this study is non-financial companies listed on the Indonesia Stock Exchange from 2013-2017. The sample was selected using the purposive sampling method, with a total sample of 150 companies. Data analysis is done through path analysis. The results showed that foreign ownership structure has a negative and significant effect on myopic behavior, audit quality has a negative and significant effect on myopic behavior, and foreign ownership structure has a positive and not significant effect on firm value. Other findings show that audit quality has a positive and significant effect on firm value, Myopic behavior has a negative and significant influence on firm value. However, myopic behavior does not play a role in mediating the structure of foreign ownership of firm value, and on the other hand, myopic behavior plays a role in mediating the quality of audits of firm valueThis study aims to examine the effect of foreign ownership structure and audit quality on firm value that is tested directly or through myopic behavior. The sample used in this study is non-financial companies listed on the Indonesia Stock Exchange from 2013-2017. The sample was selected using the purposive sampling method, with a total sample of 150 companies. Data analysis is done through path analysis. The results showed that foreign ownership structure has a negative and significant effect on myopic behavior, audit quality has a negative and significant effect on myopic behavior, and foreign ownership structure has a positive and not significant effect on firm value. Other findings show that audit quality has a positive and significant effect on firm value, Myopic behavior has a negative and significant influence on firm value. However, myopic behavior does not play a role in mediating the structure of foreign ownership of firm value, and on the other hand, myopic behavior plays a role in mediating the quality of audits of firm value.